Relationship between heavy vehicle speed limit and fleet fuel consumption on minor roads. (May 2016) - Wilson, G; Morrison, G; Midgley, W; Cebon, D
This paper investigates the traffic-related effects of a proposal to increase the speed limit from 40 mile/h to 50 mile/h, for heavy goods vehicles greater than 7.5 tonnes, on single carriageway roads. A 'microscopic' single carriageway traffic simulation is developed by combining the 'enhanced intelligent driver model' with a single carriageway gap-acceptance passing model. Fuel consumption estimates are made using engine characteristic maps and a 'fuel optimal' gear selection scheme, where vehicle trajectories from the traffic simulations are taken as input drive-cycles. Traffic congestion and fleet fuel consumption are specifically addressed, though implications regarding passing behaviour and traffic safety are also noted. Results indicate that the proposed 50 mile/h heavy goods vehicles speed limit would reduce traffic congestion by over 37% and increase fleet fuel consumption by approximately 0.5 L/100 km.